Empowering the Market Economy through Innovation and Entrepreneurship - Samli, A. Coskun (Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2016)
This book argues that the strength of our dynamic society is a market economy, which functions well only if positive and constructive marketing practices are performed. It offers innovative alternatives for achieving economic progress and outlines strategies to create conditions for equal opportunity. The American economy has transitioned from a "survival of the fittest" to "survival of the fattest" mentality, focusing less on the people and quality of life and more on the amount of dollars to be gained. The divide between the 1% and 99% leaves lower-income individuals at a significant disadvantage and threatens both economic and societal advancement. The author offers clear, intelligible solutions to accomplish this such as eliminating discrimination, providing opportunities for new ideas and industries, enhancing quality of life, and encouraging more competition so that radical innovations can emerge and make a positive difference. This book will appeal to leaders and researchers across marketing, economics, management, and accounting looking for answers on how to get the American economy back on track.